Carbapenemase gene detection using Xpert Carba-R in a tertiary care hospital among extremely drug resistant gram-negative bacilli. (March 2022) - Sheth, D.; Kothavale, S.; Gaikwad, V.; Pardeshi, P.; Kukreja, S.; Pujari, A.
Abstract : Purpose: Carbapenems serve as the 1 st line drugs for the treatment of drug resistant gram-negative bacilli (GNB) infections. However, carbapenem resistance (CR) among GNB is quite common in India. CR can be due to enzymes called as Carbapenemases e.g. (New Delhi Metallo-beta-lactamase (NDM-1), Klebsiella pneumoniae carbapenemase (KPC), oxacillin-hydrolysing β-lactamases (oxacillinases) OXA-48, Verona Integron-Mediated Metallo-β-lactamase (VIM), Imipenemase (IMP) or due to porin channels or efflux pumps. With the availability of novel beta-lactam/beta-lactamase inhibitors (BL/BLIs) specifically acting in presence of some carbapenemase e.g., Ceftazidime avibactam for OX48 producers, laboratory detection of these genes may help improve patient outcomes by tailoring therapy. This study was conducted for understanding the molecular epidemiology of Carbapenemase producing GNB in a tertiary care hospital Methods & Materials: A retrospective study was conducted from Jan 2020 to June 2021 in the Microbiology Dept of a 221-bed tertiary care hospital. Xpert Carba-R (GeneXpert Cepheid, USA) was performed on significant isolates that indicated CR on automated drug susceptibility testing (Vitek 2 Compact, Biomeriuex, France). Carba-R test was performed using pure colonies according to the manufacturer guidelines of Xpert Carba-R. Results: We performed Carba-R on 57 isolates: 33 blood culture, 9 respiratory, 6 tissue, 6 intraabdominal and 3 urine isolates. 43/57 (75.4%) were intensive care unit (ICU) patients. 46/57 (80.7%) isolates had one or more carbapenemase genes. They were as follows: 18/46 (39%) OXA-48, 12/46 (26%) NDM, 13/46 (28.2%) both OXA48 and NDM, 1/46 (2.1%) both VIM and NDM. Klebsiella pneumoniae (Kpn) was the most common isolate with CR, 37/46 (80.4%). The most frequent genes encountered in Kpn were OXA 48, 17/37 (46%) followed by OXA 48 and NDM, 13/37 (35%). There were 11/57(19.2%) isolates which were Carbapenem resistant on VITEK but none of the resistant genes were detected possibly due to other resistant mechanism like efflux pump and porin channels. Conclusion: This study indicated that carbapenemase genes are an important concern in our ICU. Klebsiella pneumoniae and OXA 48 were the most frequent isolate and carbapenemase gene encountered in our study.